Fear of falling does not predict self-reported physical activity: an observational study with community-dwelling older adults - Aoyagi, Giovana A.; Pinto, Rafael Z.; Lemes, Ítalo R; Pastre, Carlos M. [UNESP]; Eto, Bianca Y. [UNESP]; Faria, Maíra S [UNESP]; Morelhão, Priscila K.; Franco, Márcia R (Elsevier, 2022)
OBJECTIVES: To investigate the relationship between FOF and self-reported physical activity levels among older adults. DESIGN: Observational cross-sectional. SETTING AND PARTICIPANTS: Community-dwelling older adults aged 60 years and over and without cognitive deficits were recruited. MAIN OUTCOME MEASURES: Data collected included cognitive function [i.e., Mini Mental Status Examination (MMSE)], FOF [i.e., Iconographic Falls Efficacy Scale (Icon-FES); Falls Efficacy Scale - International (FES-I)], self-reported physical activity (i.e., Modified Baecke Questionnaire for Elderly People), history of falls, number of comorbidities and clinical tests of balance and mobility (i.e., Short Physical Performance Battery and the single leg stance test with closed and opened eyes). Multivariable linear regression was used to test whether FOF predicts self-reported physical activity levels. RESULTS: A total of 200 older adults living in the community were enrolled in this study. Our results showed that FOF, as measured by FES-I or Icon-FES, did not predict self-reported physical activity levels in community-dwelling older adults. CONCLUSION: Our results did not support previous evidence that higher FOF predicts lower levels of self-reported physical activity. These results question the role of FOF in influencing self-reported physical activity levels among community-dwelling older adults.
Keywords: Accidental Falls; Aged; Epidemiology; Exercise